Plots of Domination, Plots of Relationality.: On the Triangular Positioning of Characters in American and European Literature - Bollobás, Enikő (AMERICANA E-journal of American Studies in Hungary, 2019)
Framed by theories of patriarchy and intersubjectivity, this essay in character studies offers a paradigm for the triadic positioning of characters in American and European literature. Two types of triangles are described, patriarchal and intersubjective, set apart along the primary parameters of hierarchy, asymmetry, fixity of gendered subject/object roles, and domination vs. non-hierarchy, reciprocity, fluidity of gendered subject/object roles, and relationality. The subject–object relations of patriarchal triangles are characterized by rigidity; their positions are hierarchical, asymmetrical, and fixed in terms gendered power as well: while men always occupy subject positions, women take object or object–mediator positions, the dominant person insists on his domination over both his rival and the desired woman. Grounded in relations with changeable positions among desiring subjects, desired objects, and mediators of desire, intersubjective triangles are characterized by non-hierarchy, shifting positions, and reciprocity or interchangeability, while the subject’s relationality is emphasized. Positions are gendered variably: men and women can equally take subject and object positions, or positions of the desiring, the desired, or the mediator. Desire can be owned by woman as much as man can be the object of desire.